2013
DOI: 10.1590/s1678-86212013000200009
|View full text |Cite
|
Sign up to set email alerts
|

Influência do procedimento de mistura em laboratório nas propriedades de argamassas

Abstract: A mistura dos materiais sólidos com a água é uma das etapas mais importantes no preparo das argamassas. A condução do procedimento que é adotado interferirá nas propriedades no estado fresco, assim como no endurecido. A Norma ABNT NBR 13276:2005 indica que os materiais sólidos sejam introduzidos no líquido já disposto no recipiente. Essa ordem de introdução dos materiais é o inverso do que ocorre na prática e pode resultar na falta de homogeneidade da mistura. Estudos anteriores observaram que adicionar o líqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…Correlating the results of the concrete slump test with addition of fresh residue obtained by Soares [36] and the yield stress of cement pastes obtained in present study, Table 10 and Figure 10 were established. It is important to mention here that the correlation is done using the results of slump tests obtained by Soares [36] for concrete in the fresh state while the present study shows values of yield stress of the cement phase of these concretes, ie, only water mixed with cement and OSR residue, using the same type of cement and w/c ratio for the two studies.…”
Section: Correlation Between Rheological Parameters Of the Cement Pasmentioning
confidence: 56%
See 1 more Smart Citation
“…Correlating the results of the concrete slump test with addition of fresh residue obtained by Soares [36] and the yield stress of cement pastes obtained in present study, Table 10 and Figure 10 were established. It is important to mention here that the correlation is done using the results of slump tests obtained by Soares [36] for concrete in the fresh state while the present study shows values of yield stress of the cement phase of these concretes, ie, only water mixed with cement and OSR residue, using the same type of cement and w/c ratio for the two studies.…”
Section: Correlation Between Rheological Parameters Of the Cement Pasmentioning
confidence: 56%
“…According to some researchers, the mixing time is one of the factors that influence the paste homogenization. França et al [36,37] have shown in their research that samples with longer mixing times demonstrate more efficiency, producing more fluid and stable mortars.…”
Section: Determination Of the Mixing Procedures For The Production Of mentioning
confidence: 98%
“…Os teores de 40% e 60% apresentaram comportamento bem parecido, com grande parte da deformação plástica e atingindo em seguida o enrijecimento por deformação. A ocorrência do estágio II está relacionada ao comportamento de argamassas de fácil aplicação e espalhamento [15]. A curva do teor de 80% também apresentou dificuldade de escoamento, logo atingindo o enrijecimento por deformação, ou seja, pouca trabalhabilidade e enrijecimento brusco, sendo impossível a sua aplicação [16].…”
Section: Resultsunclassified
“…Immediately after mixing, the mortars are subjected to a rotational shear cycle with the same rheometer setup used for mixing (impeller geometry and planetary configuration). the shear cycle, as well as, the hysteresis area (the difference between acceleration and deceleration curves) that regards the stability condition of the material, therefore, also indicating the mixing efficiency provided by the procedure applied [27].…”
Section: Rheological Evaluationmentioning
confidence: 99%